Hydrodynamic and Geostress Controls on CBM Enrichment in the Anze Block, Southern Qinshui Basin, North China - Dameng Liu; Zheng Zhao; Xiaoming Jin; Chao Yang; Wei Chen; Yidong Cai; Yongkai Qiu; Yuejian Lu; Yingfang Zhou (Geofluids)
The coalbed methane (CBM) resource in the southern Qinshui Basin, North China, is abundant. Proper understanding of the geological control factors on CBM enrichment in Anze Block of southern Qinshui Basin is critical to design efficient CBM development plan in this area. Field and laboratory data including well logging, well testing, hydraulic fracturing, and groundwater chemical analysis of were used to evaluate the characteristics of the hydrodynamic and geostress, and then, the combined effect of hydrodynamic and geostress field on CBM enrichment was analyzed. The results show that the total dissolved solids (TDS) of groundwater in the west is generally lower than that in other areas in the block, and the primary formation water is NaHCO3-type. The geostress field shows a σH>σv>σh dominated geostress type in this area, and the western block has a lower value than the eastern block. The strong hydrodynamic field with low TDS also has a lower gas content while the weak hydrodynamic field with high TDS has a higher gas content. Both the TDS value and the horizontal stress differences are positively related to the gas content, indicating that inactive hydrodynamics and large horizontal stress difference of coal reservoir is favorable for CBM preservation.